1996
DOI: 10.1002/bjs.1800830722
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the management of critical limb ischaemia

Abstract: A prospective study of all patients with critical limb ischaemia (CLI) who presented to a single vascular unit was undertaken for a 12-month period. There were 222 referrals in 188 patients, 80.2 per cent of which were emergency or urgent admissions. The majority (72.5 per cent) were initially investigated with colour duplex scanning to characterize the arterial lesion. Diagnostic angiography was performed in 35.1 per cent. An attempt at revascularization was made in 73.0 per cent of cases using percutaneous t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
23
2
1

Year Published

1998
1998
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(29 citation statements)
references
References 9 publications
3
23
2
1
Order By: Relevance
“…1012 This may be due to patients with diabetes having increased disease severity. 13 Despite this, our study did not demonstrate an association between diabetes and risk of amputation.…”
Section: Discussionmentioning
confidence: 99%
“…1012 This may be due to patients with diabetes having increased disease severity. 13 Despite this, our study did not demonstrate an association between diabetes and risk of amputation.…”
Section: Discussionmentioning
confidence: 99%
“…The Leicester group have shown that 42.3% of patients with CLI can be treated with angioplasty alone, with a further 6.3% treated by a combination of bypass and angioplasty. 21 In attempting to hone our own indications for SA, we now consider claudication to be a relative contraindication. Although our morbidity from intervention in claudicants was low, there were three technical failures, of whom two required elective bypass surgery.…”
Section: Discussionmentioning
confidence: 99%
“…In a more recent study, Yeager et al (24) reported a 70% limb salvage and 85% survival in 74 patients (92% of the patients had acute thrombosis) with acute limb-threatening ischemia treated surgically. A recently published study of 188 patients and 198 limbs with acute threatening ischemia treated with surgery, PTA, or both reported an in-hospital mortality of 10% and a limb salvage rate of 79% [25].…”
Section: Discussionmentioning
confidence: 99%